Analysis of Greenwashing Measurement on Internal Company Factors in Indonesia - Dianto Kurnia Parulian Sinaga; Zuliani Dalimunthe (Eduvest - Journal of Universal Studies, 2025)
This research addresses the critical need to understand the relationship between internal company factors and greenwashing practices in Indonesia's emerging ESG landscape. With increasing investor focus on environmental claims and regulatory scrutiny of corporate sustainability reporting, understanding the drivers of greenwashing has become essential for market transparency and investor protection. This research investigates the relationship between internal company factors and greenwashing risk using data from 30 Indonesian-listed firms on the ESG Leader index from 2021-2023. Employing a linear regression panel data model, the research examines the influence of tax ratio, state-owned enterprise status, profit margin, and capital structure on greenwashing, while controlling for firm size, cash flow, and board size. The findings indicate a significant negative relationship between profit margin and greenwashing risk, suggesting that financially healthier companies are less prone to greenwashing. A higher effective tax rate is associated with lower greenwashing activities. Conversely, cash flow from operations and firm size positively correlate with greenwashing risk. No significant influence was found for state-owned enterprise status or capital structure. The research highlights the crucial role of corporate profitability and tax management in mitigating greenwashing, while noting that larger, cash-rich firms may be more susceptible to such practices.